Removal of Cu, Cd, Zn, Ni and Fe from wastewater comparison of three different substrates used in model scaled constructed wetland - Zupančič Justin, Maja (Sanitarno inženirstvo, 2008)
Different wastewaters contain metals that, unlike organic pollutants, are not degradable in the biological treatment system. Primary removal mechanisms can be achieved via sorption with a use of effective sorption media and precipitation processes which have been well demonstrated for metal removal also in wetland environment. The aim of the study was to test substrates like sand, peat and ceramics waste particles for removal of selected metal ions in a model-scaled constructed wetland (CW). The model comprised three large compartments where sand, peat-sand mixture or ceramics waste particles were exchanged in three successive experiments. In the compartment filled with sand99.3 %, 97.8 %, 97.8 %, 97.0 %, and 32.2 % efficiency of metal removal forCu, Cd, Pb, Zn, and Ni was achieved respectively. Fe leached out of the substrate in this experiment. In the compartment filled with the mixture of peat and sand was the efficiency of metal removal for Zn 99.8 %, Cu 99.3 %, Cd98.0 %, Pb 97.9 %, Ni 95.8 %, and Fe 28.3 %, while in the compartment with ceramics the treatment efficiency reached for Cu 99.6 %, Pb 98.0 %, Cd 98.0 %,Fe 92.8 %, Zn 52.0 %, and for Ni 12.4 %. The substrates used in horizontal subsurface flow model expressed the capacity of efficient metal reduction fromwastewater and indicate on the possibility of their application in a real-scale CW as a separate, cost-efficient pre-treatment or post-treatment step in the case of additional need of metal removal from the wastewater.
Keywords: Sewage; Železo; Cink; Copper; Zinc; Vode odpadne; Baker; Nickel; Nikelj; Iron; Water Purification; Voda, čiščenje; Sanitarna tehnika; Sanitary Engineering; odpadne vode; čiščenje odpadnih voda; težke kovine